Structure and mechanism of the oestrogen receptor. - Kong, E; Pike, A; Hubbard, R (2003)
We have determined the structures of the oestrogen receptor ligand-binding domain in complex with a range of ligands and with fragments of co-regulator proteins. These structures provide insights into the structural mechanisms underlying the receptor's complex pharmacological properties and how the conformation of the receptor modulates its ability to recruit co-regulators that are necessary for transcriptional activation.